Apical pleurectomy as a technique of elimination of continuous exudation after pulmonary resection due to multiple drug resistant tuberculosis - S. A. Belov; A. A. Grigoryuk (Туберкулез и болезни лёгких)
The efficiency of apical pleurectomy after pulmonary resection due to multiple drug resistant tuberculosis has been analyzed. The time of exudation of pleural fluid and the rate of aerostasis have been compared. The average time of exudation in patients with multiple drug resistance without pleurectomy made 11.9 + 1.9 days (p < 0.05), and with pleurectomy made 6.8 ± 1.6 days (p > 0.05). Thus the apical pleurectomy significantly reduces the time of exudation.